Complete genome sequence of an ehrlichia minasensis strain isolated from cattle - Aguiar, Daniel M.; Araujo, João P. [UNESP]; Nakazato, Luciano; Bard, Emilie; Cabezas-Cruz, Alejandro (American Society for Microbiology, 2019)
Ehrlichia minasensis is a tick-borne pathogen affecting cattle, cervids, and dogs, and it is closely related to the monocytotropic pathogen Ehrlichia canis. Here, we announce the draft genome sequence of Ehrlichia minasensis strain Cuiabá, isolated from a naturally infected calf from Santo Antônio do Leverger, Mato Grosso, Brazil.